Pre‐transplant end‐stage renal disease‐related immune risk profile in kidney transplant recipients predicts post‐transplant infections. Issue 3 (21st May 2016) - Crepin, T.; Gaiffe, E.; Courivaud, C.; Roubiou, C.; Laheurte, C.; Moulin, B.; Frimat, L.; Rieu, P.; Mousson, C.; Durrbach, A.; Heng, A.‐E.; Saas, P.; et al.
Abstract: Background: End‐stage renal disease (ESRD) is associated with premature aging of the T‐cell system. Nevertheless, the clinical significance of pre‐transplant ESRD‐related immune senescence is unknown. Methods: We studied whether immune risk phenotype (IRP), a typical feature of immune senescence, may affect post‐transplant infectious complications. A total of 486 patients were prospectively studied during the first year post transplant. IRP was defined as positive cytomegalovirus serology with at least 1 of the following criteria: CD4/CD8 ratio <1 and/or CD8 T‐cell count >90th percentile. Results: We found that 47 patients (9.7%) had pre‐transplant IRP. IRP+ patients did not differ from IRP− patients for any clinical characteristics, but exhibited more pronounced immune senescence. Both opportunistic infections (43% vs. 6%, P < 0.001) and severe bacterial infection (SBI) (40% vs. 25%, P = 0.028) were more frequent in IRP + patients. In multivariate analysis, IRP was predictive of both opportunistic infection (hazard ratio [HR] 2.97 [95% confidence interval CI 1.53–5.76], P = 0.001), and SBI (HR 2.33 [95% CI 1.34–3.92], P = 0.008). Acute rejection rates were numerically much lower in IRP+ patients. A total of 418 patients (86%) had biological evaluation 1 year post transplant. Among 41 IRP+ patients, 35 (85%) remained IRP+ 1 year post transplant. Conclusion: Pre‐transplant IRP is associated with an increased risk of post‐transplant infection.